[PP.17.12] LONG TERM VARIATIONS OF CREATININE IN ESSENTIAL HYPERTENSIVES. (September 2017) - Gosse, P.; Cremer, A.; Boulestreau, R.; Gaillard, P.; Papaioanou, G.; Lainé, M.
Abstract : Objective: The way renal function may decline with time in benign essential hypertension is still a matter of debate. This evolution was studied in a prospective registry of essential hypertensive patients untreated at baseline and then treated with various antihypertensive treatments. Design and method: Among a registry of 1200 essential hypertensives, we selected all patients with baseline normal renal function (eGFR MDRD> = 60 ml/min/1.73m 2 ), no diabetes and no proteinuria and with at least one other creatinine dosage available at least 10 years apart from baseline. Results: 433 patients were thus selected (231 males, 202 females, aged 51 ± 11 years at inclusion with baseline creatinine = 83 ± 15 μmoles/l and eGFR = 82 ± 15). Average follow up was 18 ± 5 years. Average creatinine change was not significant (0 ± 27). A creatinine level > = 130 μmoles/l was recorded in 12 patients (2.8%) with only one terminal renal failure and dialysis. 46 showed an increase in creatinine of at least 20 μ moles. In all cases but two this increase was abrupt from a dosage to another and not progressive along the whole survey. The figure illustrates the variation of creatinine levels in patients with a creatinine increase of at least 20 μmoles and at least 3 different creatinine measurements during follow up. Figure. No caption available. A stepwise discriminant analysis showed that baseline office pulse pressure (PP) (p = 0.003), age (p = 0.001) and baseline eGFR (p < 0.001), but not PP at follow up or survey lasting were significant predictors of such an increase in creatinine level. Conclusions: There is no systematic increase in creatinine levels in benign essential hypertensives. Around 10% of patients showed a creatinine increase of at least 20 micromoles during follow up but this increase was abrupt and not slowly progressive